Psychoactive Drug MDMA - Amit Prasad Rath (Journal of Community Pharmacy Practice, 2024)
MDMA, commonly known as ecstasy or molly, is a synthetic psychoactive drug with a complex history. It produces feelings of increased empathy, emotional connection, and heightened sensory perception. While recreational use of MDMA has been prevalent, recent research suggests significant therapeutic potential in treating mental health conditions like post-traumatic stress disorder (PTSD). This thesis will explore the pharmacological effects of MDMA, its historical and cultural significance, the current state of research on its therapeutic applications, and the ongoing debate regarding its legal status.